Socioeconomic determinants and pregnancy outcomes among adolescent mothers: A cross-sectional study in a tertiary care hospital in Amalapuram. - Chillapalli, Chamundeswari; Hasamnis, Dr. Varada A.; Vijaya, Chaganti (Student’s Journal of Health Research Africa, 2025)
Background: Adolescent pregnancy remains a major public health concern, particularly in developing countries, due to its association with adverse maternal and fetal outcomes. Various socioeconomic and educational factors significantly influence its prevalence and complications. Objectives: To assess the socioeconomic status and pregnancy outcomes of adolescent mothers and to identify key factors influencing maternal and fetal health. Methods: A prospective cohort study was conducted at KIMS and RF, Amalapuram, from November 2023 to November 2024. Fifty adolescent pregnant women (≤19 years) attending the OPD and labour room were included. Data regarding sociodemographic variables and pregnancy outcomes were collected using a semi-structured proforma and analyzed using SPSS version 22. Results: Most adolescent mothers (60%) were aged 18–19 years, and 70% were primigravida. A majority belonged to the upper-lower (40%) and lower (30%) socioeconomic classes. Anemia (40%) and IUGR (36%) were the most common antenatal complications. Preterm birth (24%) and IUGR (20%) were the predominant fetal outcomes. Postpartum complications included PPH (12%) and puerperal sepsis (8%). Conclusion: Adolescent pregnancy is more prevalent among socioeconomically disadvantaged, less-educated, and married teenage girls, with notable maternal and fetal complications. Strengthening adolescent education and healthcare access is vital. Recommendations: Implement adolescent health education, enforce child marriage laws, and improve access to antenatal care in rural areas to reduce complications.